Methodological approach to the quantitative assessment of risk caused by a collision between birds and aircraft - A. G. Guziy; A. P. Kostina (Научный вестник МГТУ ГА, 2022)
Since 2011 worldwide, and since 2014 in Russia, a trend has revealed a steady increase in the number of aviation events caused by a collision between birds and civil aircraft. The article presents the results of the bird aircraft strike hazard (BASH) analysis in commercial aviation in Russia and proposes a methodological approach to the quantitative risk assessment caused by bird strikes. The process of the quantitative assessment of the risk level resulted from bird strikes, implemented within the framework of the UTair Aviation Safety Management System on the results of 2021, is described. The estimation of the probability is provided for aviation events of all the possible severity levels: an aircraft incident, serious accident, major accident, fatal accident. In the empirically obtained formulas for the indirect probability estimation of aircraft occurrences, the conditional probability of aviation events of greater severity was used, if events of lower severity took place, in accordance with the ratios in the previously obtained “risk pyramid” of commercial aviation in Russia. Solving the problem of quantifying the risk level contributes to increasing the assessment reliability due to the transition from a three-level risk ranking (“acceptable”, “tolerable”, “unacceptable”) to a twenty-five-level ranking and makes it possible to evaluate the effectiveness of corrective actions aimed at reducing risk by comparing the quantitively assessed level of residual risk with the original one; to optimize risk management according to the effectiveness criterion of corrective actions according to the criterion “increment in the risk level/cost”, to identify high-risk aerodromes in advance and plan unscheduled checks of ornithological aerodrome support; to develop and implement preventive corrective measures to improve ornithological support at high-risk aerodromes; to update periodically the recommendations to flight personnel in the event of a bird strike and a threat of collision (especially during takeoff and landing). The proposed methodological approach ensures the functioning of the risk management loop in the flight safety management system of any aircraft operator when performing a monthly risk analysis associated with seasonal and regional BASH in Russia.